PENGEMBANGAN LEMBAR KERJA SISWA (LKS) DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION UNTUK MENINGKATKAN MINAT BELAJAR DAN HASIL BELAJAR SISWA - Ludgardis Gunu Bayo; St Muthmainnah Yusuf; Nur R Adawiyah Mahmud (MEGA: Jurnal Pendidikan Matematika, 2020)
This research aims to develop student worksheets with team assisted individualization (TAI) cooperative learning models in Pythagoras Theorem materials. This research aims to find out the increased interest in learning and student learning outcomes. The method used in this study uses research and development (R & D) method with ADDIE (Analysis, Design, Development, Implementation, Evaluatio) design. The data collection techniques used in this study are questionnaires, validation sheets and study results tests. Instruments used are device validation sheets, student response questionnaires, student learning interest questionnaires and student learning outcomes. The data analysis technique used is qualitative data consisting of advice and comments from experts and qualitative data judging by the analysis of validity, practicality and effectiveness. The results showed that, learning devices were declared very valid with the average assessment results from experts 4.15, the student response questionnaire reached 73.81% which is intended in the positive category so that the developed LKS is declared practical, the student learning interest questionnaire reached 70.33% that is in the positive category as well as the results of students who reach an average of 81.66% that exist in the complete category.